Perspektif Sosiologi Hukum Islam tentang Kekuatan Yuridis Normatif Kompilasi Hukum Islam dalam Penerapannya pada Putusan Pengadilan Agama - Triana Apriyanita; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the Islamic legal sociology perspective regarding the normative juridical strength of the Compilation of Islamic Law (KHI) in its application to religious court decisions in Indonesia. The KHI serves as a structured legal guideline with the primary goal of creating uniformity in legal practices within religious courts. An analysis of court decision documents referring to the KHI was conducted to understand the application of these norms in practice. The results reveal that the implementation of the KHI is not solely determined by formal norms but is also influenced by social factors, such as local values, societal perceptions of law, and the dynamics of interaction between judges, lawyers, and litigants. The normative juridical strength of the KHI in religious court decisions is significantly shaped by the social and cultural context of the community. The application of Islamic law must take into account local values and existing social dynamics, enabling the KHI to function as an adaptive instrument that bridges law with societal realities. Thus, this study provides a significant contribution to understanding the interaction between law and society within Indonesia’s religious court system.